2018
DOI: 10.1002/cbic.201800608
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Fluorophore Aggregates for the Selective Detection of Albumins in Solution and on Electrophoresis Gels

Abstract: We report a fluorescent probe that is highly sensitive and selective for serum albumins. Signal transduction results from the disassembly of fluorescence‐quenched aggregates upon binding to human serum albumin (HSA). The probe offers a rapid (≤2 s) fluorometric assay of HSA in phosphate‐buffered saline, urine, or blood serum with a high signal‐to‐noise ratio. It is also useful as a wash‐free prestaining reagent for detecting HSA on electrophoresis gels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For example, the fluorescence intensity at 538 nm increases 18‐fold ( F / F 0 ) in viscous glycerol relative to that of fluid ethanol solution (Figure 6b). Moreover, a related target binding‐induced deaggregation and rigidification has previously been invoked to rationalize the fluorogenic responses of CV derivatives in the presence of other biomacromolecules [65] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the fluorescence intensity at 538 nm increases 18‐fold ( F / F 0 ) in viscous glycerol relative to that of fluid ethanol solution (Figure 6b). Moreover, a related target binding‐induced deaggregation and rigidification has previously been invoked to rationalize the fluorogenic responses of CV derivatives in the presence of other biomacromolecules [65] …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a related target binding-induced deaggregation and rigidification has previously been invoked to rationalize the fluorogenic responses of CV derivatives in the presence of other biomacromolecules. [65]…”
Section: Photophysical Underpinnings Of the Fluorogenic Responsementioning
confidence: 99%
“…Related cyanine dyes were recently described by Park et al [35] that are said to respond to serum albumins via the disassembly of fluorescence-quenched aggregates of dyes 1, 2 and 3 as shown in figure 4. It cannot be excluded, though, that the effects additionally are caused by the replacement of the cyano groups (which have a reactivity close to that of some chloro substitutents) with lysine amino groups in the albumins.…”
Section: Polymethine Chameleon Labelsmentioning
confidence: 99%
“…Because of the amphoteric behavior of histidine at neutral pH, it can easily participate in the π interactions with other amino acids and cations in proteins . Involving the imidazole ring in the catalytic sites of many metalloproteins and enzymes, histidine directly plays important roles in human biochemistry. Misregulation in the levels of histidine-rich proteins is connected to several diseases, such as liver cirrhosis, low heart function, malaria, genetic thrombophilia, AIDS, renal diseases, pulmonary disorders, asthma, etc. Different techniques such as immunoassays, colorimetry, fluorescence, , high performance liquid chromatography (HPLC), and thin-layer or gas chromatography are available for detecting histidine and histidine-rich proteins. Although reports ae available on detecting human serum albumin (HSA) or bovine serum albumin (BSA), a few articles reported fluorescence turn-on sensing of various histidine-rich proteins. ,, For example, Wong et al reported a luminescent iridium complex as a histidine-specific probe used to stain histidine-rich proteins .…”
Section: Introductionmentioning
confidence: 99%